Harmonizing Islamic Law and Local Culture: A Study of The Mampatangpulo Tradition in Duri, Enrekang Regency - Rahmawati, Rahmawati; Muhajir, Muhammad Nur Alam; Assad, Andi Sukma; Abdain, Abdain; Taudiyah, Nasya Tisfa (Jurnal Ilmiah Al-Syir'ah, 2024)
This research thoroughly examines the relationship between customary law and Islamic law and how they relate to Mampatangpulo. This type of research is qualitative, and the research location is in Enrekang Duri, where a sociological and phenomenological approach is used. The data in this research comes from primary and secondary data, while the data collection techniques used in this research use observation, interviews, and documentation. Data is processed and analyzed using data reduction techniques, presentation, and conclusion drawing. The results of this research show that the process of implementing the Mampatangpulo Tradition starts from the Sangbonginna, Mangbongi tallu, Mangbongi pitu events and the peak of the Mampatangpulo event after the death of the deceased. In the process of implementing the Mampatangpulo Tradition, several stages of traditional processions are considered sacred and essential to carry out, namely Mangpepellao (Lowering), Mampakande-kande (Feeding), Manggere' beke (Slaughtering a goat). The Mampatangpulo tradition can only be carried out if the procession does not violate Islamic law. According to a review of Islamic law regarding the implementation of the Mampatangpulo tradition, the law is okay when the procession does not violate Islamic law because, in the implementation of the Mampatangpulo tradition that developed in the people of South Sulawesi, there are habits that have positive values. This research also shows a strong relationship between customary law and Islamic law in the Mampatangpulo tradition, such as in the takziah and friendship events. The results of this study confirm that the culture that develops in Indonesian society and globally can be preserved if it does not conflict with Islamic values.